Assessment of the construct of paranoia in a non-clinical sample: validation of the paranoia scale based on a continuum model - Maryam Amini Fasakhoudi; Abbas Masjedi Arani; Abbas Bakhshipour Roudsari; Maryam Mazaheri; Asma Shahi; Saina Fatollahzadeh; Mohammad Kazem Atef Vahid (BMC Psychology)
Abstract Objectives This study aimed to evaluate the psychometric properties of the Persian version of the Paranoia Scale (PS) in a sample of university students. Specifically, we assessed its structural validity, measurement invariance, reliability, and other psychometric characteristics to determine suitability for use in Persian-speaking populations. Methods A total of 470 university students were recruited using a convenience sampling method over a six-month period. Participants completed the Paranoia Scale and other measures which were conceptually related to the concept of paranoia. Data analysis comprised descriptive statistics, correlation coefficients, measurement invariance, as well as principal component analysis and confirmatory factor analysis. Results Principal component analysis (PCA) revealed a two-factor structure, comprising “Mistrust Thoughts” and “Persecutory Ideas.” Subsequently, a second-order confirmatory factor analysis (CFA) demonstrated an acceptable model fit, supporting the scale’s structural validity. Conclusions Paranoid thoughts in non-clinical populations are phenomena of interest in their own right and may increases our understanding of delusions. Therefore, the Paranoia Scale suggest as a valid and reliable instrument with good internal consistency.